Pengembangan Modul Pembelajaran Berbasis Group Investigation Dengan Pendekatan Problem Based Learning Pada Mata Kuliah Sistem Akuntansi Mahasiswa Pendidikan Ekonomi Universitas Nusantara PGRI Kediri - Efa Wahyu Prastyaningtyas, Hestin Sri Widiawati (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2018)
Lecture accounting system is a course that must be taken by students of economiceducation. Initial observations made by the researcher show that the textbooks owned by thestudents are still not adequate, so the learning process can not be maximized, especially theteaching materials in the form of print. The research and development of this accountingsystem module aims to realize the practical learning materials, effective and has relevance tothe needs of students. Learning accounting system module developed based on groupinvestigation as research product. The model used in the development of this learning tool isBorg and Gall Model. Broadly speaking step development research consists of three stages:1) Preliminary study phase, 2) Development study phase 3) Evaluation Phase. The data havebeen analyzed descriptively quantitatively using inferential statistics using control groupand experimental group. The results obtained that the learning-based group investigationmodule with a problem-based learning approach in the course of effective accounting systemis reviewed from the results of understanding the concept and test results of students. This isbecause the module developed is made interesting with communicative and simple languageso that it can be understood by the student.